PEMBUATAN PLANG SELAMAT DATANG SEBAGAI BENTUK PENGABDIAN KKN KELOMPOK 4 UNIVERSITAS NIAS RAYA TAHUN 2025 DI DESA HILIFAROKHA LAWA KECAMATAN FANAYAMA KABUPATEN NIAS SELATAN - Pradiance Mindo W. Duha; Amelinda Wau; Yusta Yusnyaman Giawa; Oktavianus Bali; Fernando J. Hondro5; Alvin Ndruru; Nelan halawa; Sergius S.P haria; Yulianus Laia; Priskan Maduwu; Lies Dian Marsa Ndraha (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity serves as a meaningful learning medium for students in developing social responsibility, cooperation, and concern for rural community development. Through direct involvement in the field, KKN students learn to understand the real needs of the community and contribute in concrete ways. One of the work programs carried out by KKN students in Hilifarokha Lawa Village is the construction of a “Welcome” sign that functions as both a village identity marker and an information medium. This program was motivated by the absence of a representative village sign, which caused the identity of Hilifarokha Lawa Village to be less visible to visitors and people from outside the area. This condition encouraged the KKN students to provide a simple yet beneficial solution through the creation of a welcome sign. The presence of this sign is expected to provide initial information about the village and create a positive impression for anyone entering the village area. The implementation of the activity was carried out through several planned stages, starting from field observation, coordination with the village government, planning the sign design, to the process of construction and installation. All stages were conducted in a participatory manner by involving the local community, thereby fostering a sense of ownership, togetherness, and the spirit of mutual cooperation. The results of the activity show that the welcome sign not only functions informatively and aesthetically, but also increases the community’s pride in their village. Thus, this activity is expected to provide sustainable benefits for Hilifarokha Lawa Village and serve as a tangible form of student community service.